Functional Study of SAMD9L in Familial Gastric Cancer - Kaixuan, Xu; Xiaobin, Zhang; Jiaxuan, Tang; Shihui, Liu; Xinxin, Wang; Shuwei, Hu; Penggao, Dai; Xiang, Luo (Turkish Journal of Gastroenterology, 2023)
Background: Familial aggregation occurs in approximately 10% of cases of gastric cancer. The genetic predisposition or cause of the disease in only about 40% of hereditary gastric cancer cases is known, while the genetic factors of the remaining cases remain to be studied. Methods: Samples were collected from a family with gastric cancer, including 3 gastric cancer and 17 healthy samples. Whole-exome sequencing was performed on samples from 3 patients with gastric cancer and 1 sample from healthy peripheral blood. SAMD9L was knocked down using small interfering RNAs and short hairpin RNA. The expression of SAMD9L was detected by quantitative real-time polymerase chain reaction and Western blot in SGC-7901 cells. CCK-8 assay was used to detect the proliferation of gastric cancer cells. The migration and invasion of gastric cancer cells were detected by Transwell assay and scratch assay. The cell apoptosis was detected by flow cytometry. Results: Twelve single-nucleotide variants and 9 insertions/deletions mutation sites were identified as candidate genes. Among them, SAMD9L regulates cell proliferation as a tumor suppressor gene. The experiments of knocking down SAMD9L in SGC-7901 cells revealed that reduced expression of SAMD9L significantly enhanced the proliferation, migration, and invasion of SGC-7901 cells. Conclusions: These results suggest that SAMD9L inhibits the proliferation of gastric cancer cells, thereby increasing the risk of gastric cancer in people with SAMD9L downregulation. Therefore, SAMD9L may represent a susceptibility gene of this gastric cancer family. Cite this article as: Kaixuan X, Jiaxuan T, Shihui L, et al. Functional study of SAMD9L in familial gastric cancer. Turk J Gastroenterol. 2023;34(5):472-482.